Pelatihan Pengelolaan Keuangan untuk Keluarga : Mengelola Resiko dan Cerdas Finansial - Saragih, Susanti; Widiastuti, Ratna; Zaniarti, Sri; Margaretha, Yolla; Kristine, Fanny; Nursalin, Kezia Kurniawati; Margaretha, Meily; Lu, Cen (Jurnal Pengabdian UNDIKMA, 2024)
This community service activity aims to increase the knowledge and skills of parents of Bandung Baptist Christian Junior High School students regarding families' financial planning and management to avoid family financial risk. This community service implementation method uses training with 25 participants, who are parents of students. The evaluation of this community service activity was carried out by conducting a survey to measure the reaction of participants, their knowledge level, and their change intention. Descriptive analysis was performed on the data collected.Â The results of the community service activity showed that more than 96% of the participants who attended found the activity relevant to their conditions. Additionally, 62% of the participants experienced an increase in knowledge regarding the concept of financial management, and all participants committed to taking concrete actions to improve their family's financial conditions, including avoiding debt, making financial records, using an application to simplify financial management, and setting a budget (financial prioritization).